KECERNAAN BAHAN ORGANIK, SERAT KASAR DAN LEMAK KASAR PAKAN AYAM PEDAGING YANG DIBERI TEPUNG LIMBAH LABU KUNING (Cucurbita moschata) - Moningkey, Andre F.; Wolayan, Fenny R.; Rahasia, Cathrien A.; Regar, Mursye N. (Universitas Sam Ratulangi, 2019)
DIGESTIBILITY OF THE ORGANIC MATTER, CRUDE FIBER AND CRUDE FAT IN BROILERS RATION CONTAINING PUMPKIN WASTE MEAL (Cucurbita moschata). A research was done to determine the digestibility values of feed in term of organic matter, crude fiber and crude fat containing pumpkin waste meal (PWM) fed to broilers. The research was conducted by involving 20 unsexed broilers, strain CP 707 at 5 weeks old with an average body weight of 1073 g. Experiment design of the Completely Randomized Designed (CRD) was applied with 4 treatments and 5 replications at each treatment. Honestly significant difference test (HSD) was used to define higher significant effects of the treatments. The treatments consist of 100% basal ration (BR) + 0% PWM (R0), 95% BR + 5% PWM (R1), 90% BR + 10% PWM (R2) and 85% BR + 15% PWM (R3). Results showed that digestibility of crude fiber was significantly affected by treatments (P<0.01), but digestibility values of organic matter and crude fat were not influenced by these treatments. The statistical test showed that the crude fiber digestibility of R0 (56.92%) was lower than those of R1 (63.10%), R2 (67.71%) and R3 (66.30%). Furthermore, there was no difference among digestibility values of Â R1, R2 and R3. Based on this research, it can be concluded that pumpkin waste meal could be utilized to replace some parts up to 15% in ration of broilers.Â Keyword: Pumpkin waste meal, digestibility, broiler